Chemistry and Biology of the Potent Endotoxin from a Burkholderia dolosa Clinical Isolate from a Cystic Fibrosis Patient. Issue 9 (3rd June 2013) - Lorenzo, Flaviana Di; Sturiale, Luisa; Palmigiano, Angelo; Fazio, Luigi Lembo‐; Paciello, Ida; Coutinho, Carla P.; Sá‐Correia, Isabel; Bernardini, MariaLina; Lanzetta, Rosa; Garozzo, Domenico; Silipo, Alba; Molinaro, Antonio
Abstract This is the first report of the chemical and biological properties of the lipooligosaccharide (LOS) endotoxin isolated from Burkholderia dolosa IST4208, an isolate recovered from a cystic fibrosis (CF) patient in a Portuguese CF center. B. dolosa is a member of the Burkholderia cepacia complex, a group of closely related species that are highly problematic and opportunistic pathogens in CF. B. dolosa infection leads to accelerated loss of lung function and decreased survival. The structural determination of its endotoxin was achieved using a combination of chemistry and spectroscopy, and has revealed a novel endotoxin structure. The purified LOS was tested for its immunostimulatory activity on human HEK 293 cells expressing TLR‐4, MD‐2, and CD‐14. In these assays, the LOS showed strong proinflammatory activity.